A Practical Theology Tool to Identify Subjective Individual and Group Spiritual Perspectives - Hennessy, Deborah Anne (Practical theology, 2015)
This article explains the adaptation of a social science method called Q into a practical theology tool which elicits the spiritual experiences and perspectives of individuals or groups; offering potential for deepening personal understanding of one's inner life. Q-methodology uses a combination of qualitative and quantitative techniques based on statements which are drawn from the literature about the subject and in consultation with key stakeholdersin this case, spirituality. The statements are then prioritized by participants using a grid and commenting on their choices. Sets of spiritual narratives emerge from the analysis and reflect participants' key experiences of faith and life. This tool has a number of valuable uses including a transformational opportunity. The tool was developed for a specific cohort (Anglicans in the Western Cape, South Africa); however, it is readily transferable to many other cultural contexts.